Impact sound insulation technique using corn cob particleboard - Faustino, J.
A low technological corn cob particleboard has been under research by this research team. It intends to be affordable and sustainable. So far, some of its assessed material properties (e.g. density, fire resistance, durability, thermal conductivity, compression and bending strengths, and impact resistance) suggest adequacy of this product for several building applications, such as a thermal insulation product, a light weight partition wall, a ceiling coating, or as indoor doors, among other possibilities. However, proper acoustic insulation performance is also a fundamental property required for most of the above identified building applications. Therefore, this paper is focused on evaluating the impact sound insulation potential of the proposed particleboard. At this stage, impact sound insulation tests have been performed in which the acoustic insulation gain of a pavement reinforced acoustically by a 3 cm thick corn cob particleboard was assessed. The obtained acoustic insulation gain was then compared with the respective ones of traditional sound insulation products (e.g. glass wool and expanded polystyrene) and also with different alternative natural sound insulation products (e.g. kenaf, coco fibre, sheep wool, cork and cellulose). The obtained results indicate that the proposed product may also have an interesting acoustic behaviour for building purposes. This conclusion is even more interesting taking into account that corn cob is a natural, organic, renewable and local raw building material.